Etnogenesis dan Kehidupan Keagamaan Migran Muslim di Malaysia - Wong, Diana; Aziz, Arfan (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2013)
The dynamics of religious life and the formation of ethnic identity after Malaysia independence is the starting point of this paper. Malaysiaâs rapid economic development in 1970s invites Indonesia labor migration and other Asian countries like India, Bangladesh and Myanmar, which then bring together with them the religious culture of their homeland and significant changes in the religious discourse of citizens. This article made from the research that has been conducted on religious lives of two migrant communities in Malaysia and aimed to describe the relationship between religious lives of citizens below the Islamic Malay ethno genesis which took place under the Malaysian nation-state regime. Although the migrants and citizens both are Muslims, this study shows âthe homeâ for both sides precisely in the transnational missionary movements, especially, Tablighi Jamaat which will be further elaborated after the next discussion of this article. Keywords: Kehidupan keagamaan, Migran, Etnogenesis.